Exploring logics of state in urban cultural policy development process in South Africa: the case of the eThekwini Municipality - Maralack, Matthieu (My University, 2019)
The study of urban cultural policy development is a relatively new field of enquiry, particularly in the Global South. The goal of this study is to understand urban cultural policy development and state practice through unpacking a South African case study of a local municipality undertaking such a process between the period 2012 to 2016. Notably, this particular case of cultural policy development did not result in a policy being approved by council, nor in administrative operations. The specific question asked therefore is: “How is cultural policy development contested between different arms of the local state, in the case of eThekwini?”. Namely: between the eThekwini City Architects Department and the Parks, Recreation and Culture Department. This is answered by giving a historical account of how the process came about by extensively drawing on one specific moment prior to the policy development timeline. It is the case of the Warwick elephant sculpture by world-renowned artist Andries Botha, which highlights the ANC and IFP political tensions which were not successfully negotiated, alongside several other contextual challenges. The literature that informs the conceptual framework is that of the theoretical challenge with the terms culture and cultural policy, where creativity and culture intersect with the urban state, and the concept of championship with the South African urban state context. Methodologically, semi-structured interviews were utilised as part of the qualitative data collection and case study approach. This was triangulated through the use of a document analysis. The research report directly addresses how ANC-IFP tensions impacted urban governance and cultural policy development in eThekwini and concludes with the type of championship needed for successful cultural policy development in this context for the benefit of future cultural policy development processes in the Global South.
Submitted in partial fulfilment of the requirements for the degree of Master of Arts in Cultural Policy and Management, to the Faculty of Humanities, University of the Witwatersrand, Braamfontein March 2019
Keywords: Cultural policy; Urban renewal--South Africa; South Africa--Cultural policy